Strategic Management and Customer Relationship Building Strategies to Enhance Business Potential Case Study: A Modern Boutique Hotel in the Eastern Region - Tiyapunjanit, Prachern (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to study strategic management and customer relationship building strategies to enhance business potential case study: a modern-style boutique hotel in the Eastern region. This study was qualitative research, the case study approach was adopted. Data were collected with the help of an in-depth interview from 30 participants, which consisted of 10 modern-style boutique hotel business executives in the Eastern region and 20 customers who had received the service at a modern style boutique hotel. The results of the study showed that in the aspect of strategic management, hotel managers complied with hotel management strategies, namely planning, organizing, commanding, coordinating, and controlling, to achieve efficiency in corporate management. In terms of customer relationship management, to increase the potential, the hotel integrated customer service system, marketing automation, sales automation, and customer data warehouse to manage customer relationships. They utilized these devices both online and offline to increase the potential of modern boutique hotels. From the study, we can apply the research findings to improve hotel management strategies as a guideline for creating modern boutique hotel management strategies in the Eastern region. In addition, these findings are able to be adapted as a guideline for entrepreneurs and those who are interested in investing in this business in order to improve management in their organizations.